ANALISIS MULTI KRITERIA DALAM PEMILIHAN UNIT BIOLOGIS DI IPAL TUNGGAKJATI, KARAWANG - Sa’dman, Ceihan Arkan; Astuti, Ariani Dwi; Hadisoebroto, Rositayanti (Jurnal Lingkungan dan Kota, 2023)
This study aims to design a domestic wastewater treatment plant for the West Karawang and East Karawang Sub-districts in Karawang Regency, where each sub-district has an area of 13.368 Ha and 2.977 Ha. In 2041, the Tunggakjati WWTP will have a capacity of 48,000 m3/day to serve a population of 404,568 people. The WWTP performance is designed so that the effluent complies with the Regulation of the Minister of Environment and Forestry No. 68 of 2016 concerning Domestic Wastewater Quality Standards for its BOD, COD, and TSS parameter. The biological treatment design consists of three (3) alternatives namely Oxidation Ditch, Complete Mixed Activated Sludge, and Aerated Lagoon, selected based on multi criteria with three (3) aspects, namely economic, environmental and technical aspects consisting of technological considerations, land availability and human resources to operate the technology. The selected biological treatment unit alternative is Aerated Lagoon, because it has high efficiency, human resources for operating the technology are already available, and ease of development. Based on multi criteria analysis all the alternative has high eligibility level to be chosen as technology for domestic waste water treatment. Alternative III, the Aerated Lagoon is the best alternative with the highest score of 60 compared to other alternatives, alternative I is 52.5 and alternative II is 57.5. That concludes the processing units on processing units at the Tunggakjati WWTP consist of collection wells, bar screens, grit chambers, equalization tanks, aerated lagoons, maturation ponds, and sludge drying beds.